Fall Detection Using Smartphone-Based Application - Kerim YILDIRIM; Gokhan UCAR; Tahir KESKIN; Adnan KAVAK (International Journal of Applied Methods in Electronics and Computers, 2016)
Among the elderly persons and disabled citizens injuries caused by falls can be dangerous even leading to death. Fast response can improve the people’s outcome but without knowing the accident nobody can help them. Falls are more dangerous when accidents happen while the people are alone. So it is very important to inform acquaintance and caregivers at the situation like this. Our purpose here is to inform caregivers by using a device an android-based smart phone which is available everywhere or can be get easily. The method is depends on the tri-axial accelerometer integrated with the phone. The android application -evaluated with threshold based algorithm- captures data from the accelerometer when the fall occurs. Then informs the caregivers which is defined before in the settings. The algorithm first asks the user and waits for a dedicated time if he/she is all right. If he/she is not responding the application will send an e-mail, make a phone call to inform the caregivers etc…